Biotic homogenization of oceanic islands depends on taxon, spatial scale and the quantification approach. Issue 5 (6th February 2020) - Otto, Rüdiger; Fernández‐Lugo, Silvia; Blandino, Cristina; Manganelli, Giuseppe; Chiarucci, Alessandro; Fernández‐Palacios, José María
Abstract : Biotic homogenization reduces the regional distinctiveness of biotas with signiﬁcant ecological and evolutionary consequences. The outcome of this process may depend on the spatial scale of inquiry (both resolution and extent), the selected taxon and dissimilarity index as well as on the contribution of species extinctions and introductions. In the present research, we try to disentangle the effects of these factors on homogenization patterns comparing six taxonomic groups (pteridophytes, spermatophytes, breeding birds, mammals, reptiles and non‐marine molluscs) within and between five Atlantic archipelagos of the Macaronesian Region. Taxonomic homogenization was analyzed by partitioning β‐diversity into spatial turnover of species composition and nestedness. Total compositional change was divided into changes related to extinctions/extirpations of native and to introductions of alien species. Analyses were carried out at two different spatial resolutions (island versus archipelago unit) and geographic extents (within each archipelago and across the whole Macaronesian Region). Pteridophytes and reptiles tended to taxonomic differentiation, while mammals and molluscs showed homogenization regardless of scale and resolution. For spermatophytes, the most species‐rich group, taxonomic heterogenization traded off with homogenization from the local to regional extent. Birds revealed heterogenization at the island, but not at the archipelago resolution. Extirpations of native species generally led to homogenization at the local extent, whereas the effect of alien introductions varied according to taxon and spatial scale. Furthermore, overall changes in species pool similarities were driven both by spatial turnover and nestedness. We demonstrate that biotic homogenization after human colonization within Macaronesia clearly depended on taxon, spatial scale and the dissimilarity measure. We suggest that homogenization of island biotas is first conditioned by initial dissimilarity related to taxon characteristics, such as dispersal capacity or endemicity, evolutionary processes, archipelago configurations and environmental variation along spatial scales. Thus, similarity change is the outcome of the impacts of number, proportion and distribution type of lost and gained species. Rare extirpated and common introduced species homogenize, while common extirpated and rare introduced species differentiate island biotas. Partitioning of beta diversity helps to improve our understanding of the homogenization process.